The death of Chaos - Modesitt, L. E., Jr., 1943- (Modesitt, L. E., Jr., 1943- Saga of Recluce., 1995)
In the continuing war between order and chaos, a young carpenter who is a magician is asked by his country to use his powers to defend the land from invaders. The call provokes jealousy in his wife who is one of the country's top military leaders. By the author of The Magic of Recluse.